1983
DOI: 10.1093/nar/11.19.6803
|View full text |Cite
|
Sign up to set email alerts
|

HMG 14/17 binding affinities and DNAase I sensitivities of nucleoprotein particles

Abstract: We show that ordinary (bulk) chicken erythrocyte nucleosomes are digested more rapidly by DNAase I when they are associated with high mobility group (HMG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1984
1984
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…A number of observations indicate that HMG proteins have a structural role in chromatin. They are relatively abundant (_ 106 copies per nuclei, Goodwin et al, 1978a) and some of these fractions, HMG-14 and -17, have conformational effects on nucleosomes; these may be related to the DNase I sensitivity of specific zones of chromatin (Weisbrod et al, 1980;Stein and Townsend, 1983). In the case of HMG-1 and -2 less defined hypotheses have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of observations indicate that HMG proteins have a structural role in chromatin. They are relatively abundant (_ 106 copies per nuclei, Goodwin et al, 1978a) and some of these fractions, HMG-14 and -17, have conformational effects on nucleosomes; these may be related to the DNase I sensitivity of specific zones of chromatin (Weisbrod et al, 1980;Stein and Townsend, 1983). In the case of HMG-1 and -2 less defined hypotheses have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the increased sensitivity of active chromatin domains to DNase I correlates with the presence of HMG-14 and/or HMG-17 (7,27). However, whether HMG-17 and HMG-14 are directly responsible for the increased DNase I-sensitivity is controversial (28)(29)(30)(31)(32). As an immature B-cell, DT40 expresses large amounts of immunoglobulin light-chain proteins from the rearranged copy of its λ light-chain gene.…”
Section: Lack Of Null-mutation Effects On Dnasei-hypersensitive Sitesmentioning
confidence: 99%
“…However, the subject is a matter of controversy (see e.g. Nicolas et al, 1983;Seale et al, 1983;Stein and Townsend, 1983;Swerdlow and Varshavsky, 1983), in part due to experimental discrepancies but also caused by an extrapolation of data obtained from welldefined components, like chicken erythrocyte mononucleosomes, to more complex systems. Nevertheless, studying nucleosomal organization within domains of transcribed chromatin requires understanding of these phenomena.…”
Section: Introductionmentioning
confidence: 99%